OPTIMALISASI KETRAMPILAN MOTORIK KASAR MELALUI PERMAINAN EGRANG TEMPURUNG KELAPA - Prolesari, Prolesari; Madyawati, Lilis; Pujiastuti, Febru (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2014)
Objective singer is aware optimization of gross motor skills through games stilts coconut shell IN Kindergarten Tunjungsari Kesugihan IN Group B Age 5-6 Years.The study was conducted WITH Draft Action Research (PTK) AT Students Group B Kindergarten Tunjungsari Kesugihan Purwodadi District of Purworejo, WITH 3 Children research subjects. Singer study using three variables ie input variables, process variables, output variables. The data were collected using Observation Sheet And Interview Guide. Data Validity WITH THE triangulation How Indicators 65%.CONCLUSION The study findings Singer Was Rough motor skills can be optimized through Coconut Shell Game stilts.Article Search Google showed changes increase gross motor skills through games stilts coconut shell. It Cantor proved their findings WITH EACH change cycle. The findings achievement counting capability subjects I initially Being 17.6% 72.6% 12.5% subjects II Originally INCREASED 74%, 22.2% subjects III Original Being 73%. Hypothesis ?Rough motor skills ON Protégé kindergarten through Optimal Tunjungsari stilts Coconut Shell Game,? Proven truth.